Depression in acute and chronic aphasia: symptoms, pathoanatomical-clinical correlations and functional implications. Issue 6 (June 1993) - Herrmann, M; Bartels, C; Wallesch, C W
Abstract : Depressive alterations were investigated in 21 acute and 21 chronic aphasic patients with single left sided strokes. The assessment of depression was based on a psychometrically evaluated German version of the Cornell Scale for Depression (CDS) and the Research Diagnostic Criteria (RDC). No significant difference was found concerning depression sum-scores between the two aphasic groups. The acute group, however, exhibited significantly higher ratings in items related to physical signs of depression and disturbances of cyclic functions. Patients corresponding to the RDC-syndrome of major depression were only found in the acute group. Neither age, sex nor degree of hemiparesis discriminated the patients on the severity of depressive symptoms. In the acute patient group, nonfluency of aphasia was the only parameter that could be identified which had an effect on the mood symptom scores. A CT scan analysis in the acute patient group showed an association between the severity of depression and anterior lesions. A significant correlation was found between CDS sum-scores and the proximity of the anterior border of the lesion to the frontal pole of the hemisphere whereas the volume of lesions seemed to have no effect on depressive alterations in acute aphasic patients. Superimposition of the lesions of the aphasic patients with major depressive disorders showed a common subcortical lesion area involving putaminal and external pallidal structures.